Poverty, Business Strategy, and Sustainable Development. (December 2016) - Hart, Stuart; Sharma, Sanjay; Halme, Minna
The past 15 years have witnessed an exponential growth in business activities aimed at serving the needs and increasing the well-being of disenfranchised individuals in low-income communities. Thousands of new business initiatives, development institution programs, and innovative investment funds focused on poverty alleviation have emerged during this time. Similarly, since the late 1990s when Prahalad and Hart first coined the term Bottom of Pyramid (BoP), and suggested a new, enterprise-based approach to poverty alleviation, there has also been a steady rise in research on business and poverty. A whole new lexicon emerged to describe this phenomenon, including phrases like "inclusive business, " "subsistence market places, " "frugal innovation, " and "impact investing." Unfortunately, management theory and research have not advanced at the same pace with the BoP business revolution, and consequently knowledge about parameters for successfully integrating business, poverty alleviation and sustainable development still remains ambiguous.